Wezwania lubelskich świątyń jako elementy krajobrazu sakralnego miasta - Siwiec, Adam (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2020)
The article discusses the historical and descriptive aspects of the invocations of patron saints in the Lublin churches, in the context of the city’s space and sacral landscape. Because the dominant role in Lublin’s religious life is played by the Catholic Church, the most numerous group are the names relating to Catholicism - but not exclusively: other Christian denominations (including Eastern ones) are also represented. Churches as spatial objects belong to the city’s cultural landscape, its sacral landscape and sacred space. It is a sanctity that emerges thanks to shared meanings, communicated by means of an urban and architectural code, as well as in connection with linguistic forms qua messages concerning a given object and place. Forms of this kind are invocations of patron saints associated with places of religious cult. They have a discursive marking that results from being anchored in religious discourse; however, they can also function as elements that organize the communal life of the discourse of social memory. This article deals with Catholic patron saints. The data have been classified semantically but also with respect to the form of the names and their cultural motivation. Thanks to this, they could be correlated with specific ways of the onymic impersonation of the sacred.